Perilaku Menjaga Kesehatan Genetalia berhubungan dengan Kejadian Keputihan di SMK Muhammadiyah 4 Yogyakarta - Lutfiyati, Afi (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Background: Adolescents are at risk of experiencing leucorrhoea because this period is a transitional period or a period of maturity of their sexual organs. Leucorrhoea is a problem that is often experienced by women of various ages. One of the factors that affects leucorrhea is the behavior to maintain genital health which is a self-care activity especially carried out in the female organs to avoid infection. The most commonly carried out behavior which is rarely applied is washing hands before touching the genital area. Methods: This is a quantitative research with a cross-sectional approach. The sample used is total sampling with a total of 45 female respondents. Data collection was carried out on 8 June 2022 at SMK Muhammadiyah 4 Yogyakarta. Questionnaires about the genital health behavior and the cases of leucorrhea were used as the instruments. The data collected were analyzed using the chi-square test. Results and discussion: Based on the results of the study showed that the behavior of maintaining the health of genetalia, the majority of respondents behaved well as many as 23 respondents (51.1%), the majority of respondents with physiological discharge incidence were 32 respondents (71.1%). The analysis results of the chi-square test show that there is an association between the behavior to maintain genital health and the cases of leucorrhea with p-value of 0,002 (p<0.05) (OR=10,5; 95% CI=1,969-55,998). Therefore, the respondents whose genital health behavior is poor are likely to suffer from pathological leucorrhea 10,5 times higher compared to the respondents who have a good behavior in maintaining their genital health. Conclusion: There is an association between the behavior to maintain genital health and the cases of leucorrhea at SMK Muhammadiyah 4 Yogyakarta.